Pemanfaatan Media Sosial Dalam Pemasaran Produk UKM Berbasis Lorong - A. Nur Asri Ainun; Sewang (Yayasan Habiburrahman Jamalu Bina Ummat, 2023)
Globalization is a challenge for Small and Medium Enterprises (SMEs) to survive. Information Technology, especially social media, offers benefits for SMEs to improve their marketing. This Community service was conducted to identify the use of social media and its benefits to SMEs in Lorong 310 in Mariso Village, Makassar City. From the results, the researchers found that alley 310 UKM actors had not maximized existing social media so that this activity was expected to educate Lorong-based UKM actors.